Revision of the Pantomorus albosignatus species group (Coleoptera: Curculionidae: Entiminae) from Mexico and Central America - Lanteri, Analia A.; Rio, Maria Guadalupe Del (Zootaxa, 2020)
Pantomorus albosignatus Boheman, 1840 (Entiminae: Naupactini), type species of the genus Pantomorus Schoenherr, 1840, is broadly distributed in Mexico, from Oaxaca and Veracruz to Chihuahua and Coahuila, and is probably related to P. parvulus Sharp 1891 (México: Oaxaca and Veracruz), P. andersoni sp. nov. (México: Guerrero), and P. crinitus (Boheman, 1840) (southern Mexico, El Salvador and Guatemala). The four species are small (5-8 mm), apterous, usually show a characteristic maculation and erect setae on the elytra, short antennae, vestigial to absent humeri, and well-developed, squamose corbels of the metatibiae, and are here referred to as the Pantomorus albosignatus species group. Our study was based on the examination of type material and about 500 specimens from different collections, and provides a dichotomous key, descriptions or redescriptions of the species, habitus photographs, line drawings of female and male genitalia, a map of distribution, new locality records and new plant associations. We propose that Pantomorus nobilis (Boheman 1840) is a new junior subjective synonym of P. crinitus (Boheman, 1840), and we designate lectotypes for the species Pantomorus albosignatus Boheman, P. parvulus Sharp, P. crinitus (Boheman), P. nobilis (Boheman) and P. affinis Sharp, 1891 (the latter is also a junior synonym of P. crinitus). Pantomorus albosignatus usually inhabits Acacia grasslands and cactus deserts of the Mexican Plateau, at higher elevations than remaining species; P. parvulus occurs in cloud forests and tropical deciduous forests of southern Mexico; P. crinitus in open oak pine forests, cloud forests and tropical deciduous forests of southern Mexico, Guatemala and El Salvador; and P. andersoni is endemic to the state of Guerrero, in Acacia-cactus woodlands.